Post-traumatic Stress Disorder, Depression, Anxiety Symptoms and Help Seeking in Psychiatric Staff: Trouble de stress post-traumatique, dépression, symptômes d'anxiété et recherche d'aide chez le personnel psychiatrique. (August 2020) - Seto, Michael C.; Rodrigues, Nicole C.; Ham, Elke; Kirsh, Bonnie; Hilton, N. Zoe
Background And Methods: In this study, we surveyed 761 psychiatric hospital staff (69% women, 71% full-time, 56% nursing) regarding their exposure to trauma in the workplace; symptoms of post-traumatic stress disorder (PTSD), depression, and anxiety; help seeking; and perceived barriers for help seeking. Results: Significant proportions of staff met the screening cutoffs for probable PTSD (16%), depression (20%), and anxiety (16%). Comorbidity was high, with approximately half of those meeting the screening cutoff for PTSD also meeting the cutoffs for depression or anxiety. Only PTSD symptoms were uniquely associated with exposure to trauma in the workplace, but both PTSD and depression symptoms significantly predicted help seeking. Staff who met one or more screening cutoffs perceived more barriers to help seeking such as difficulty with accessing services. Conclusion: Implications for supporting psychiatric staff exposed to trauma are discussed.